Analisis Kinerja Pegawai Di Era Pandemi Covid-19 Dalam Pelayanan Publik Pembuatan E-Ktp Dan Kartu Keluarga Di Kantor Kecamatan Rantau Pulung - Rida Ratnawati; Budiman; Melati Dama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study aims to analyze and describe Employee Performance in the Covid-19 Pandemic Era in Public Services Making E-KTP and Family Cards at the Rantau Pulung District Office and to be able to find out the supporting and inhibiting factors on employee performance in the Covid-19 Pandemic Era in providing services E-KTP and Family Card at the Rantau Pulung District Office. This research method uses a qualitative descriptive research type because it can accurately describe social phenomena, situations, conditions being observed and events, and can collect facts. The results showed that the quality of the work of employees of the Rantau Pulung District Office in making E-KTP in Rantau Pulung was not in accordance with the SOP during the pandemic which had to be done online while for Family Cards it was in accordance with the applicable SOP and for the results of making E-KTP there were still errors in address typing. The quantity of work results has not reached the target to be achieved because there are several obstacles. Employee initiative is still lacking in providing services for making E-KTP and Family Cards. Employee job satisfaction is good, it can be seen from the friendly attitude of employees. Good job knowledge can be seen from the education and abilities of each employee. Factors supporting employee performance include ability and knowledge as well as performance inhibiting factors, less stable internet network and lack of infrastructure such as a broken recording device at the Rantau Pulung District Office.